2018
DOI: 10.7554/elife.34574
|View full text |Cite
|
Sign up to set email alerts
|

Design principles of a microtubule polymerase

Abstract: Stu2/XMAP215 microtubule polymerases use multiple tubulin-binding TOG domains and a lattice-binding basic region to processively promote faster elongation. How the domain composition and organization of these proteins dictate polymerase activity, end localization, and processivity is unknown. We show that polymerase activity does not require different kinds of TOGs, nor are there strict requirements for how the TOGs are linked. We identify an unexpected antagonism between the tubulin-binding TOGs and the latti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
88
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(105 citation statements)
references
References 45 publications
(94 reference statements)
14
88
3
Order By: Relevance
“…Our observation that the bZIP allele restores kinetochore binding and viability suggest that it is homodimerization of Stu2 and not sequence specific elements within the coiled-coil domain that is important for Stu2's kinetochore functions. While previous studies showed that Stu2's in vitro microtubule binding is reduced when dimerization is prevented (Al-Bassam et al, 2006;Geyer et al, 2018), we found that the stu2 cc∆ mutant cells maintained normal spindle length in vivo. Although we cannot rule out the possibility that the stu2 cc∆ mutant has an effect on microtubule dynamics in vivo, the spindles appeared to function normally because inactivation of the spindle checkpoint allowed the stu2 cc∆ mutant cells to enter anaphase and segregate chromosomes.…”
Section: Stu2 Utilizes Multiple Domains To Achieve Kinetochore Associcontrasting
confidence: 89%
See 2 more Smart Citations
“…Our observation that the bZIP allele restores kinetochore binding and viability suggest that it is homodimerization of Stu2 and not sequence specific elements within the coiled-coil domain that is important for Stu2's kinetochore functions. While previous studies showed that Stu2's in vitro microtubule binding is reduced when dimerization is prevented (Al-Bassam et al, 2006;Geyer et al, 2018), we found that the stu2 cc∆ mutant cells maintained normal spindle length in vivo. Although we cannot rule out the possibility that the stu2 cc∆ mutant has an effect on microtubule dynamics in vivo, the spindles appeared to function normally because inactivation of the spindle checkpoint allowed the stu2 cc∆ mutant cells to enter anaphase and segregate chromosomes.…”
Section: Stu2 Utilizes Multiple Domains To Achieve Kinetochore Associcontrasting
confidence: 89%
“…Cells that expressed the stu2 cc∆ allele arrested with a spindle length (1.91 ± 0.54 μm) that was nearly indistinguishable from that of cells expressing a wild-type copy of STU2. Thus, while mutants that alter Stu2's dimerization exhibit polymerization defects in vitro (Al-Bassam et al, 2006;Geyer et al, 2018), our data indicate that this does not lead to a defect in spindle formation in vivo. Furthermore, the fact that the stu2 cc∆ mutant is defective in kinetochore binding yet supports a normal mitotic spindle provides a tool to examine Stu2's kinetochore functions in cells.…”
Section: Dimerization-deficient Mutant Of Stu2 Is Defective In Kinetomentioning
confidence: 64%
See 1 more Smart Citation
“…Current models of TOG-catalysed tubulin polymerisation all rely on the presence of multiple TOG domains in a single polypeptide or a complex (Ayaz et al, 2014;Geyer et al, 2018;Nithianantham et al, 2018;Slep and Vale, 2007). MEKK1 only contains one TOG domain, suggesting that the MEKK1 TOG domain mechanism-of-action is different to that of other TOG domains.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 23 mutants or RNAi knockdowns tested in our survey for regulators of the fat body ncMTOC, minispindles (msps) RNAi knockdown ( Figure 14B, C) singularly caused a severe defect in nuclear centricity ( Figure 14D), indicating that Msps is essential for fat body ncMTOC activity. Msps, the homolog of XMAP215/Stu2/Dis1/Alp14/ZYG-9/ch-TOG, functions at the growing MT plus end as a processive MT polymerase (Brouhard et al, 2008;Al-Bassam and Chang, 2011;Wieczorek et al, 2015;Geyer et al, 2018). Msps localizes to the fat body perinuclear MTOC ( Figure 14A, Table 1) and msps knockdown had a severe impact on radial MT assembly at the fat body MTOC.…”
Section: Msps Is Required For the Fat Body Ncmtoc Assembly Independenmentioning
confidence: 99%